Al-Takyiīf Al-Fiqhī (Fiqhī characterization) of matrimonial property in Islamic jurisprudence - Eletrebi, Mohamed Fathy; Suleiman, Hassan (American Linguist Association, 2021)
Urf (custom) and al-maṣlahah al-mursalah (public interest) are among the sources of law disputed by uṣūlīs; however, the majority of scholars are aware that public interest and its guidelines revolve around the Sharī‘ah Objectives and that custom is legally authoritative and can be referred to for judgment. It is widely known that the statement, "Al-‘ādatu Muhakkamah", is one of the major universal maxims for the Shafi‘ite school. Undoubtedly, referring to ‘Urf and al-maṣlahah al-mursalah, within the legislative framework and according to the divisions recognized by uṣūlīs, aims at the realization of the public interests, and in some cases, private interests of certain society groups. The research seeks to reach a sound fiqhi characterization (al-takyīf al-fiqhī) for the matrimonial property in view of two sources of law, namely custom and public interest, and for the rights of each spouse to the matrimonial property while marriage exists or in case of separation due to divorce of death.